Iot-enabled smart healthcare systems, services and applications - Rani, Shalli (Hoboken, NJ : Wiley, 2022)
"IoT-enabled healthcare (smart healthcare) has been under development for some time, with some of the first devices being heart monitors that automatically send data to physicians when a key event occurs or at set intervals. Wearable monitors have also offered non-intrusive technologies to enable user participation in healthcare, and easier remote monitoring of conditions. Juniper Research anticipates that the COVID-19 pandemic will accelerate adoption of IoT within the healthcare industry, and issues around security and privacy, handling data sets, reliability of devices and interoperability of systems are already coming to the fore as key challenges. New technologies such as machine learning, image processing, big data, remote monitoring, cloud computing, deep learning, and enhanced wireless communications are all improving and connecting modern healthcare services and products through IoT. https://www.juniperresearch.com/press/press-releases/iot-platform-revenue-to-grow-20-in-2020"--
Acknowledgments -- About the Editors -- List of Contributors [vendor, please compile from toc and chapter openers] -- -- Sr. No. Chapter Title Authors -- 1 Role of Emerging Technologies in Smart Healthcare -- Masooma Zehra Syeda, Dur-e-hassan ,Himanshi Babbar, masooma_zehra@hotmail.com -- -- 2 ICN-Fog computing for IoT based healthcare: architecture and challenges Divya Gupta , Shalli Rani, and Syed Hassan Ahmed -- Shalli.rani@chitkara.edu.in -- 3 Internet of Things (IoT) Enabled Software Defined Networking (SDN) for Edge Computing in Healthcare Himanshi Babbar , Shalli Rani, Neeraj Kumar -- Shalli.rani@chitkara.edu.in -- -- 4 Security and Privacy Issues in Smart Healthcare System Using Internet of Things R Nidhya, Manish Kumar, R. Maheswar, E SivaRaman -- nidhuraji88@gmail.com -- -- -- 5 An Overview of Architecture & Applications of -- IOT Based Health Care System -- M.Saravanan, J. Ajayan, R. Maheswar, Eswaran Parthasarathy -- saranecedgl@gmail.com -- 6 A Review of e-healthcare System of India and Thailand Shanu Bhardwaj, S.N. Panda, Priyanka Datta, Rajesh Kumar Kaushal, Naveen Kumar: shanu.bhardwaj@chitkara.edu.in, snpanda@chitkara.edu.in -- -- 7 WSN and IoT Based Smart Surveillance System for Patients with Closed-Loop Alarm Amit Sundas, Sumit Badotra, Shalli Rani, Chhabildas Madhukar Gajare -- shalli.rani@chitkara.edu.in -- -- 8 An IoMT based Smart Remote Monitoring System for Healthcare Chetna Kaushal, Md Khairul Islam, Anshu Singla, and Md Al Amin -- Anshu.single@chitkara.edu.in -- 9 A Multi-Domain Perspective of Future Directions for VANETs for Emergency Message Dissemination Ravneet Kaur, Ramkumar Ketti Ramachandran, Robin Doss,1 and Lei Pan1 -- rkaur@deakin.edu.au -- -- Index [list of terms to be supplied by editors at proofreading stage]
BIBINDX
Keywords: Medical informatics; Electronic books